The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnins.2020.00122
|View full text |Cite
|
Sign up to set email alerts
|

Social Jetlag and Its Association With Screen Time and Nighttime Texting Among Adolescents in Sweden: A Cross-Sectional Study

Abstract: The discrepancy between social and biological clock due to sleep and wake up time difference across weekdays and weekends is referred as social jetlag. The overall aim of this study is to test whether there is an association between both screen time and nighttime texting and social jetlag among 13-to 15-year-old adolescents in Sweden. This study included a cross-sectional survey in which data were collected from all schools with grades 7 and 8 in four municipalities in southern Sweden. The sample consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…However, broader categories of time spent on sedentary screen behaviors have been investigated. Hena and Garmy [37] found that screen time over 4 h was associated with larger social jetlag, an amount that the average European teenager has exceeded since 2002 [7]. For engaged gamers in particular, the social jetlag might be a consequence of gaming displacing sleep to a greater degree on weekends, in alignment with the observed decreased sleep duration in the weekends.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, broader categories of time spent on sedentary screen behaviors have been investigated. Hena and Garmy [37] found that screen time over 4 h was associated with larger social jetlag, an amount that the average European teenager has exceeded since 2002 [7]. For engaged gamers in particular, the social jetlag might be a consequence of gaming displacing sleep to a greater degree on weekends, in alignment with the observed decreased sleep duration in the weekends.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a trend study of sleeping difficulties among European adolescents found that screen time was significantly associated with problems falling asleep, and the relationship has strengthened over the period from 2002 to 2014 [7]. A paucity of studies has also found that screen time affects social jetlag measured as differences in weekday-weekend mid-sleep and "wake lag", measured as differences in weekdayweekend rise times [37,38]. However, no studies have looked at technology use and social jetlag defined as a difference in bedtime on weekdays and weekends [19].…”
Section: Introductionmentioning
confidence: 99%
“…Also, more than half of the students' SJL value was greater than 2 h. These results are similar to ones reported by Caumo et al (2020), here the students' SJL value was 2 h 14 min, and 59% of them had an SJL value of greater than two hours. Similarly, the SJL value was higher than 2 h in additional studies conducted with adolescents (Hena & Garmy, 2020; Mathew et al, 2019, 2020). Taken together, these data indicate that adolescents have significant sleep issues.…”
Section: Discussionmentioning
confidence: 75%
“…However, activities such as watching television, using computers, spending time on the Internet, playing electronic games, using mobile phones, and listening to music both delays and shortens the adolescents' sleep time (Cain & Gradisar, 2010). Recent studies conducted with adolescents revealed that teens engagement with electronic devices such as tablets and phones was associated with SJL (Caumo et al, 2020; Chandrakar, 2017; Hena & Garmy, 2020). Similarly, in the present study, “spending time in bed with television/computer/phone before sleeping” was found to be a risk factor for SJL ( β = 0.127; p = 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, optimal sleep quality among children and adolescents has been advocated [ 6 ]. Given changes in digital technologies and their use, use of smartphones, tablets, and other devices may interfere with sleep, as evidenced by associations between internet addiction and poor sleep in a recent meta-analysis [ 7 ] and the negative associations between screen time use and sleep [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%